Carlos Ramón Fernández Liesa, Juan Daniel Oliva Martínez, y Oscar Pérez de la Fuente (eds.), Soberanía - Arellano Pinzón, Jaelee (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
Este artículo reseña: Carlos Ramón Fernández Liesa, Juan Daniel Oliva Martínez, y Oscar Pérez de la Fuente (eds.), Soberanía, Colección Gregorio Peces-Barba, Dykinson, Madrid, 2022, 172 pp.